An early warning system for active landslides - Husaini, Omar; Ratnasamy, M. (2001)
Slope failures are commonplace in tropical countries like Malaysia. Where they affect infrastructure, an efficient and safe method for monitoring of such collapsed slopes provides an indispensable safeguard. This paper describes an early warning system that was assembled and trialed during the reconstruction of a collapsed slope at Gunung Tempurung on the North South Expressway. The magnitude of the landslide and the risk involved in the reconstruction of the active slope posed a direct challenge to researchers, academicians, consulting engineers and contractors alike. The paper explains the procedures followed for safe installation of the instrumentation over the failed slope. It also outlines the techniques used for remote management of the instrumentation and the associated early warning alarm system.